Allergen immunotherapy in atopic dermatitis - Bogacz-Piaseczyńska, Agnieszka; Bożek, Andrzej (Alergologia Polska - Polish Journal of Allergology, 2024)
The aim of this review is to investigate the possible role of allergen immunotherapy (AIT) for house dust mites in the treatment of atopic dermatitis in adult patients (AD). AIT is a commonly accepted treatment for selected allergic diseases such as allergic rhinitis, bronchial asthma, allergy to venom, and sometimes food allergy. There have been a few original reports on improving AD symptoms due to subcutaneous and sublingual immunotherapy with selected allergens, mainly house dust mites. However, the precise role of immunotherapy in treating atopic dermatitis (AD) is still not clearly defined despite some studies that have been conducted. The review discusses available studies that provide evidence of the efficacy of AIT in patients with AD who are allergic to house dust mites. The authors focused on those studies in which the indication for AIT was mainly AD and only in patients with clinically confirmed allergy to house dust mites. Despite extensive evidence of the effectiveness of such treatment, studies on large patient populations are needed to determine the exact indications for AIT in AD patients with house dust mite allergy.